The power play: Geopolitical influence on emerging market stock performance - Chin, Wei Jian; Ng, Qiao Wen; Ning, Yu Jie; Tan, Cal Ven (2025)
In this era of globalization, emerging markets have become more closely linked with global trade and capital flows, make it high growth potential but also heightened vulnerability to external shocks. Geopolitical risks are particularly important due to unpredictability and the absence of standard policy tools for mitigation. This study investigates the effect of disaggregated geopolitical risk categories, geopolitical threats and acts, and the global GPR index on sectoral and overall stock market volatility in Malaysia, Thailand, and the Philippines. Using quarterly data from 2012Q1 to 2024Q3, OLS estimation is applied with control variables such as foreign portfolio investment, lagged volatility, and market portfolio. Diagnostic tests such as normality, heteroscedasticity, and serial correlation tests are conducted to ensure the reliability and accuracy of the results. The regression results indicate that the majority of disaggregated GPR categories show statistically insignificant relationship with sectoral and overall volatility across the three markets. Only limited significant results are observed in this study, suggesting that geopolitical risks exert weaker and less systematic effects in ASEAN emerging markets compared to global evidence. Lastly, this study contributes to the literature by providing comparative sectoral evidence for ASEAN economies, offering insights for investors and academic researchers as well as deepen understanding of the complex linkages between geopolitical risks and sectoral stock market volatility. Keywords: geopolitical risk; sectoral stock market volatility; Malaysia, Thailand, Philippines; foreign portfolio investment; ordinary least squares Subject Area: HB135-147 Mathematical economics Subject Area: HG4538 Foreign investments